2021
DOI: 10.3920/jiff2019.0058
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation ofHermetia illucens larvae reared on different substrates for red tilapia diet: effect on growth and body composition

Abstract: Black soldier fly larvae (BSFL; Hermetia illucens) can be a very beneficial source of protein to replace fishmeal for fish feed, but little is known about the impact of their growing substrate on the performance and nutritional composition of the fish consuming them. In this study, BSFL were reared on two different substrates; palm oil decanter cake (DC) and coconut pulp (CP) for 35 days before processing and including them in tilapia diet with 50% inclusion level. The weight and length of the BSFL as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…While Agbohessou et al [76] and Tippayadara et al [77] found no adverse effects on the performance of tilapia when entirely replacing the FM in their control diets with BSFM, the findings of Taufek et al [78], Rana et al [79], Muin et al [80], and Devic et al [53] are in line with this study and show reduced performance above a certain level of FM replacement with 50% replacement or, in the case of [53], a BSFM inclusion of 80 g/kg diet being optimal. In this study as well, the BSF diet resulted in reduced growth and feed conversion compared to the FM diet.…”
Section: Fish Performancementioning
confidence: 91%
“…While Agbohessou et al [76] and Tippayadara et al [77] found no adverse effects on the performance of tilapia when entirely replacing the FM in their control diets with BSFM, the findings of Taufek et al [78], Rana et al [79], Muin et al [80], and Devic et al [53] are in line with this study and show reduced performance above a certain level of FM replacement with 50% replacement or, in the case of [53], a BSFM inclusion of 80 g/kg diet being optimal. In this study as well, the BSF diet resulted in reduced growth and feed conversion compared to the FM diet.…”
Section: Fish Performancementioning
confidence: 91%
“…Likewise, it showed SSI in WG and SGR in a single diet where such raw material was used as a meal [76]. Furthermore, in a single case study with different evaluated diets SSS was reported in FCR [81].…”
Section: General Considerationsmentioning
confidence: 80%
“…On average, the protein content of insect meal is 50-82% dry matter depending on the species and processing method, compared to ≤73% in fishmeal and ~50% in soybean meal (Henry et al, 2015). The lipid content of insects is generally high (10-49%) (Makkar et al, 2014) and is influenced mainly by diet and species (Galassi et al, 2021;Taufek et al, 2021;Van Huis et al, 2020).…”
Section: Insect-based Crustacean Feedmentioning
confidence: 99%